M2TeO3 internal infiltration heat modified lithium-containing positive electrode active material as well as preparation and application thereof in lithium ion battery
Through the M2TeO3 internal heat loss modification technology, the structure and surface of the cathode material of lithium-ion batteries are optimized, which solves the shortcomings of the material in terms of wide temperature range and air resistance stability, and achieves the improvement of the high- and low-temperature performance and stability of the material.
Patent Information
- Application Number
- CN202411644951.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-11-18
AI Technical Summary
The existing lithium-ion battery positive electrode materials have shortcomings in terms of wide temperature domain stability and air resistance, and it is difficult to meet the needs of high energy density, high power density and thermal stability.
M2TeO3 is used as a modifier and lithium-containing positive electrode active material for internal heat modification. Through the biphasic migration behavior of M, Te and Li, the structure and surface of the material are optimized to achieve the improvement of high-temperature and low-temperature performance.
It significantly improves the wide temperature domain stability and air resistance of the material, improves the tap density and cyclic stability of the material, and is suitable for wide temperature domain application requirements.
Smart Images

Figure CN119560550A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery positive electrode materials, and in particular to the field of lithium ion battery positive electrode material modification. Background Art
[0002] In order to reduce the consumption of non-renewable resources and carbon monoxide emissions, the research focus of lithium-ion batteries has shifted to high energy density batteries. The requirements for high energy density, high power density and thermal stability of lithium-ion batteries continue to increase, highlighting the importance of advanced lithium-ion battery technology.
[0003] With the rapid growth of the demand for large reversible capacity, high safety and long-cycle stability of lithium-ion batteries, in recent decades, more and more explorations have focused on the development of high-performance positive electrode materials. At present, lithium-ion battery positive electrode materials such as lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate and ternary materials are limited by the requirements of low specific capacity, high cycle stability and low cost. Although lithium-rich manganese-based materials have high specific capacity and low cost, their poor structural stability and voltage attenuation have hindered their commercialization. In order to solve the above problems, researchers have done a series of modification work on lithium-ion battery positive electrode materials, mainly including surface coating, element doping, single crystalization and concentration gradient structure design.
[0004] For example, a patent application document with publication number WO2021167409A1 discloses a positive electrode active material having ultrafine grains and highly oriented primary particles and a lithium secondary battery comprising the same, wherein the positive electrode active material includes a material prepared by calcining a lithium compound with a composite metal hydroxide containing any one or more of nickel (Ni), cobalt (Co), manganese (Mn) and aluminum (Al), wherein the heteroatom is added together with any one or more of nickel (Ni), cobalt (Co), manganese (Mn) and aluminum (Al), or added together with the lithium compound before calcination. For another example, a patent application document with publication number WO2021042986A1 discloses a positive electrode active material, which includes a main particle and an oxide coating layer containing the M1 element coated on the outer surface of the main particle, wherein the main particle includes a lithium composite oxide containing nickel; the bulk phase of the main particle is uniformly doped with the M2 element; the surface layer of the main particle is an external doping layer doped with the M3 element; the M1 element and the M3 element are each independently selected from one or more of Mg, Al, Ca, Ce, Ti, Zr, Zn, Y and B, and the M2 element includes one or more of Si, Ti, Cr, Mo, V, Ge, Se, Zr, Nb, Ru, Rh, Pd, Sb, Te, Ce and W.
[0005] In summary, although there are some Te doping methods in the prior art, they are mainly internal doping methods. This solution can improve the performance of the material to a certain extent, but it is difficult to give full play to the function of Te and it is difficult to further optimize the wide temperature range stability and air resistance stability of the active material. Summary of the invention
[0006] In order to solve the existing problems, the present invention provides a 2 TeO 3 A method for thermally modifying a lithium-containing positive electrode active material (also referred to as a modified active material or a modified positive electrode active material in the present invention) is intended to utilize M 2 TeO 3 The internal infiltration thermal modification method improves the wide temperature range stability and air resistance stability of the positive electrode material.
[0007] The second object of the present invention is to provide M obtained by the method 2 TeO 3 Intracellular thermally modified lithium-ion battery cathode active materials and their applications in lithium-ion batteries.
[0008] The third object of the present invention is to provide a method comprising: 2 TeO 3 A lithium-ion battery and a positive electrode and a positive electrode material thereof comprising a lithium-ion battery positive electrode active material modified by internal infiltration heat.
[0009] M 2 TeO 3 A method for preparing a lithium-containing positive electrode active material subjected to internal thermal infiltration modification, comprising: 2 TeO 3 Mixing and heat-modifying at a temperature of 200 to 800° C. to obtain a modified positive electrode active material;
[0010] The M 2 TeO 3 Wherein M is at least one of Na, K, and Rb.
[0011] The present invention innovatively combines M 2 TeO 3 As a modifier, the lithium-containing positive electrode active material is combined with the internal infiltration thermal modification, so that M and Te can be gradually infiltrated from the outside to the inside (the outer surface of the active material bulk phase to the bulk phase direction), and in this process, Li in the bulk phase is promoted to be transferred to the surface by exchange and participate in the construction of the surface modification layer in situ. The internal infiltration thermal modification and the joint control of parameter conditions described in the present invention can enhance the high-temperature and low-temperature performance of the modified active material based on the two-phase exchange migration of the components, making it suitable for wide temperature range application requirements. Not only that, it can also effectively improve the material's tap density and air resistance stability.
[0012] In the present invention, the lithium-containing positive electrode active material is a positive electrode active material suitable for lithium-ion batteries, for example, it can be a lithium-containing salt of a transition metal, and further can be one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium manganese silicate, lithium iron silicate, lithium iron phosphate, lithium nickel phosphate, lithium cobalt phosphate, high-nickel ternary material, and lithium-rich manganese-based positive electrode material.
[0013] In the present invention, the M 2 TeO 3 The molar ratio of the transition metal in the lithium-containing positive electrode active material is 0.01-0.1:1, preferably 0.03-0.05:1.
[0014] Preferably, the lithium-containing positive electrode active material, M 2 TeO 3 Compounding by dry or wet method.
[0015] In the present invention, the atmosphere in the thermal modification stage is an oxygen-containing atmosphere, for example, air, oxygen, or a mixture of oxygen and diluent.
[0016] In the present invention, the temperature of thermal modification is 450 to 650°C, and may be 500 to 600°C.
[0017] In the present invention, the heating rate in the thermal modification stage is 1-10°C / min, preferably 1-3°C / min, and further can be 1.5-2.5°C / min. The present invention has shown that controlling at this preferred rate can further improve the interface physical and chemical structure of intrapenetration and surface exchange, and can reduce the interface impedance, which helps to further improve the structural stability of the material and improve its cyclic stability under a wide temperature range.
[0018] In the present invention, the heat treatment time is 3 hours or more, preferably 4 to 8 hours.
[0019] After heat modification and heat preservation, the temperature is lowered to room temperature to obtain the modified positive electrode active material, wherein the cooling rate is 1-10°C / min, preferably 1-3°C / min, and further can be 1.5-2.5°C / min. The present invention shows that controlling the preferred cooling rate can reduce material segregation and reduce interface impedance, which helps to further improve the structural stability of the material and improve its cycle stability under a wide temperature range.
[0020] The present invention also provides a kind of M prepared by the preparation method. 2 TeO 3 Lithium-containing positive electrode active materials modified by endogenous thermal infiltration.
[0021] The preparation method of the present invention can endow the prepared material with special physical and chemical characteristics, and the material prepared by the preparation method can unexpectedly endow the modified material with excellent high-temperature and low-temperature cycle properties and air resistance stability.
[0022] The present invention also provides a positive electrode material for a lithium ion battery, comprising a positive electrode active material, which comprises the M 2 TeO 3 Lithium-containing positive electrode active materials modified by endogenous thermal infiltration.
[0023] The positive electrode material of the present invention, except for the modified active material of the present invention, may have conventional components, and the proportions and contents of the components may be reasonably regulated based on conventional principles.
[0024] For example, the positive electrode material further includes a conductive agent and / or a binder.
[0025] In the present invention, in the positive electrode active material, the M 2 TeO 3 The content of the internally thermally modified lithium-containing positive electrode active material is above 50wt.%.
[0026] The content of the positive electrode active material in the positive electrode material is 60-90wt.%.
[0027] The present invention also provides a positive electrode of a lithium ion battery, comprising a current collector and a positive electrode material composited on the surface of the current collector, wherein the positive electrode material is the positive electrode material of the present invention.
[0028] The present invention also provides a lithium ion battery, which comprises the positive electrode of the present invention.
[0029] Beneficial Effects
[0030] The present invention innovatively adopts M 2 TeO 3 The lithium-containing positive electrode active material is thermally modified from the outside to the inside, so that the structure and surface of the material can be optimized based on the dual-phase migration behavior of M, Te and Li, so that the high-temperature and low-temperature performance of the modified active material can be enhanced to make it suitable for wide temperature range application requirements. Not only that, it can also effectively improve the material's tap density and air resistance stability. In addition, the combined control of the heating rate and / or cooling rate in the thermal modification stage can further optimize the interface of the infiltration, which helps to further enhance the wide temperature range performance and stability of the prepared material. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The figure is a comparison of the cycle performance between Example 1 and the comparative example; DETAILED DESCRIPTION
[0032] Embodiment 1:
[0033] Step 1:
[0034] The lithium-rich material precursor (such as Mn 0.667 Ni 0.333 (OH) 2 ) was mixed with lithium carbonate, wherein TM:Li=1:1.5, and after being mixed evenly, sintered at 500°C for 5 hours and then at 900°C for 15 hours to obtain a lithium-rich manganese-based positive electrode material Li 1.5 Mn 0.667 Ni 0.333 O 2 (positive electrode active material).
[0035] Step 2:
[0036] 1g of lithium-rich manganese-based cathode material Li 1.5 Mn 0.667 Ni 0.333 O 2 It was mixed with sodium tellurite (modifier) in ethanol with a Te:TM molar ratio of 1:100 (TM refers to the transition metal element in the positive electrode active material). The ethanol was evaporated to dryness at 70°C, and the obtained solid powder was sintered in air. The temperature was increased to 600°C at a rate of 2°C / min and kept for 5h, and then cooled to room temperature at a rate of 5°C / min to obtain a modified material.
[0037] test:
[0038] The modified lithium-rich manganese-based positive electrode material prepared by the above method, acetylene black and PVDF were mixed uniformly in a mass ratio of 8:1:1 to form a slurry, which was evenly coated on an aluminum foil and cut into positive electrode sheets with a diameter of 12 mm. Lithium metal foil was used as the negative electrode, Celgard 2400 was used as the separator, and 1M LiPF6 EC / DMC (volume ratio 1:1) solution was used as the electrolyte. The CR2016 button battery was assembled in a glove box filled with argon, which is the battery of Example 1.
[0039] Comparative Example 1
[0040] Compared with Example 1, the only difference is that the treatment in step 2 is not performed, and the Li in step 1 is directly used. 1.5 Mn 0.667 Ni 0.333 O 2 As the positive electrode active material, other operations and parameters are the same as in Example 1.
[0041] For comparison, pure lithium-rich manganese-based material samples were assembled into CR2016 button cells under the same conditions, which is the battery of comparative example 1. The above two batteries were subjected to charge and discharge cycle tests under the same test equipment and test conditions, wherein the test voltage range was 2~4.7V, and the cycle tests were carried out at 25℃ and 0.5C. Figure 1 After the battery of Example 1 cycles 200 times, the stability is improved from 78.70% of the battery of Comparative Example 1 to 83.03%, and the cycle performance is significantly improved.
[0042] The modified material (the material obtained in step 2 of Example 1) and the original material (the material obtained in step 1 of Example 1) were placed in a 50°C constant temperature oven and a -30°C constant temperature oven respectively for high and low temperature cycle performance tests, and the voltage range of the test was 2~4.7V. In the cycle test under the conditions of 50° and 0.5C, the comparative example 1 could only perform 97 cycles (short circuit), however, the capacity retention rate of the material of Example 1 was 80.47% after 200 stable cycles. In the cycle test under the conditions of -30°C and 0.5C, after 200 cycles of the battery of Example 1, the stability was improved from 71.32% of the battery of Comparative Example 1 to 81.45%, and the high and low temperature performance was significantly improved.
[0043] After placing Comparative Example 1 and Example 1 in O2 and CO2 atmospheres (volume ratio of 1:1) for different periods of time, the crystallinity and surface morphology of Comparative Example 1 changed significantly. Li2O and Li2CO3 phases were generated in the Comparative Example 1 material, respectively. After the material was exposed to O2 and CO2 atmospheres for 24 hours, the initial capacity of the first cycle dropped rapidly from 245.3mAh / g to 169.4mAh / g. The crystallinity and structure of Example 1 were almost unchanged, showing good air stability. The first cycle capacity dropped from 249.5mAh / g to 235.67mAh / g. The battery was assembled according to the method of Example 1 for the material stored for 24 hours and cycled 200 times at 0.5C / 25℃. The stability of the material after storage in Example 1 increased from 69.28% of the battery in Comparative Example 1 to 82.55%.
[0044] Embodiment 2:
[0045] Compared with Example 1, the only difference is that the conditions of step 2 are changed. The difference step is: 1g of lithium-rich manganese-based positive electrode material Li 1.5 Mn 0.667 Ni 0.333 O 2Mix with potassium tellurite in ethanol, Te:TM=0.5:100, evaporate the ethanol at 70°C, sinter the obtained solid powder in air, heat to 500°C at a rate of 2°C / min and keep at that temperature for 6h, then cool to room temperature at a rate of 5°C / min to obtain a modified material. Other operations, parameters and tests are the same as those in Example 1.
[0046] The results showed that the retention rate of the modified material was 83.1% after 200 cycles at 25℃ and 0.5C, 80.21% after 200 cycles at 50℃ and 0.5C, and 80.78% after 200 cycles at -30℃ and 0.5C; and 83.01% after 200 cycles at 25℃ and 0.5C after 24h exposure to O2 and CO2.
[0047] Embodiment 3:
[0048] Compared with Example 2, the only difference is that in step 2, after the heat preservation is completed, the temperature is lowered to room temperature at a rate of 3°C / min to obtain the modified material. Other operations, parameters and tests are the same as those in Example 2.
[0049] The results are as follows: the retention rate of the modified material is 85.53% after 200 cycles at 25°C, 83.16% after 200 cycles at 50°C and 0.5C, and 82.95% after 200 cycles at -30°C and 0.5C.
[0050] It can be seen from Examples 2 and 3 that the process of the present invention combined with the cooling rate can further enhance the intraosmotic replacement effect of the material and further enhance the wide temperature performance of the material.
[0051] Embodiment 4:
[0052] Compared with Example 2, the only difference is that the type of positive electrode active material is changed. Specifically, the difference step is: 1g of high-nickel positive electrode material LiNi 0.8 Co 0.1 Mn 0.1 O 2 Mixed with sodium tellurite in ethanol, Te:TM=0.5:100, evaporated the ethanol at 70℃, sintered the obtained solid powder in air, heated to 500℃ at a rate of 2℃ / min and kept for 6h, then cooled to room temperature at a rate of 8℃ / min to obtain the modified material. The retention rate of the modified material after 200 cycles was 86.53%, which was better than the original sample before modification (LiNi 0.8 Co 0.1 Mn 0.1 O 2). After 200 cycles at 50°C and 0.5C, the retention rate was 85.32%, and after 200 cycles at -30°C and 0.5C, the retention rate was 82.65%.
[0053] Embodiment 5:
[0054] Compared with Example 2, the only difference is that in step 2, the heating rate in the roasting stage is 5°C / min, and the other operations and parameters are the same as those in Example 2.
[0055] The retention rate of the modified material after 200 cycles at 25°C and 0.5C was 79.23%, after 200 cycles at 50°C and 0.5C was 79.01%, and after 200 cycles at -30°C and 0.5C was 78.65%.
[0056] It can be seen from Examples 2 and 5 that at the preferred heating rate, the wide temperature performance of the prepared material can be further enhanced.
[0057] Comparative Example 2
[0058] Compared with Example 1, the only difference is that lithium tellurite is used as the modifier, and other operations and parameters are the same as those in Example 1.
[0059] The results showed that the retention rate of the modified material was 79.35% after 200 cycles at 25°C and 0.5C, 70.34% after 200 cycles at 50°C and 0.5C, and 71.25% after 200 cycles at -30°C and 0.5C.
[0060] Comparative Example 3
[0061] Compared with Example 1, the only difference is that sodium silicate is used as the modifier (the molar amount of Si is the same as Te), and the other operations and parameters are the same as Example 1.
[0062] The results showed that the retention rate of the modified material was 80.14% after 200 cycles at 25°C and 0.5C, 72.56% after 200 cycles at 50°C and 0.5C, and 71.15% after 200 cycles at -30°C and 0.5C.
[0063] Comparative Example 4
[0064] Compared with Example 1, the only difference is that the modifier of step 2 is mixed with the raw material of step 1, the treatment of step 1 is carried out, and then the temperature treatment of step 2 is carried out, and the modifier is no longer added in step 2. Other operations and parameters are the same as in Example 1.
[0065] The results showed that the retention rate of the modified material was 77.95% after 200 cycles at 25°C and 0.5C, 73.21% after 200 cycles at 50°C and 0.5C, and 74.21% after 200 cycles at -30°C and 0.5C.
[0066] In summary, the intravasation process described in the present invention can obtain excellent wide temperature performance. On this basic technology, the combined control of the heating rate and the cooling rate can further enhance the intravasation effect, which helps to further enhance the wide temperature stability and structural stability of the prepared material.
Claims
1. A method for preparing a lithium-containing positive electrode active material modified by thermal infiltration of M2TeO3, characterized in that: The lithium-containing positive electrode active material and M2TeO3 are mixed and heat-modified at a temperature of 200 to 800°C to obtain a modified positive electrode active material; The M in the M2TeO3 is at least one of Na, K and Rb.
2. The method for preparing the lithium-containing positive electrode active material by thermal infiltration modification of M2TeO3 according to claim 1, characterized in that: The lithium-containing positive electrode active material is a positive electrode active material suitable for lithium-ion batteries, preferably one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium manganese silicate, lithium iron silicate, lithium iron phosphate, lithium nickel phosphate, lithium cobalt phosphate, high-nickel ternary material, and lithium-rich manganese-based positive electrode material.
3. The method for preparing the lithium-containing positive electrode active material by thermal infiltration modification of M2TeO3 according to claim 1, characterized in that: The molar ratio of M2TeO3 to the transition metal in the lithium-containing positive electrode active material is 0.01-0.1:1, preferably 0.03-0.05:1; Preferably, the lithium-containing positive electrode active material and M2TeO3 are compounded by a dry method or a wet method.
4. The method for preparing the lithium-containing positive electrode active material by thermal infiltration modification of M2TeO3 according to claim 1, characterized in that: The atmosphere during the thermal modification stage is an oxygen-containing atmosphere.
5. The method for preparing the lithium-containing positive electrode active material by thermal infiltration modification of M2TeO3 according to claim 1, characterized in that: The temperature of thermal modification is 450~650℃, and can further be 500~600℃; Preferably, the heating rate in the thermal modification stage is 1 to 10°C / min, preferably 1 to 3°C / min, and further can be 1.5 to 2.5°C / min; Preferably, the heat treatment time is more than 3 hours, preferably 4 to 8 hours.
6. The method for preparing the M2TeO3 endothermally modified lithium-containing positive electrode active material according to claim 1, characterized in that: After heat modification and heat preservation, the temperature is lowered to room temperature to obtain the modified positive electrode active material, wherein the cooling rate is 1-10°C / min, preferably 1-3°C / min, and further can be 1.5-2.5°C / min.
7. A lithium-containing positive electrode active material obtained by the preparation method according to any one of claims 1 to 6 and subjected to thermal infiltration modification of M2TeO3.
8. A positive electrode material for a lithium ion battery, comprising a positive electrode active material, characterized in that: The positive electrode active material comprises a lithium-containing positive electrode active material that is thermally modified by infiltration of M2TeO3 and obtained by the preparation method according to any one of claims 1 to 6; Preferably, the positive electrode material further comprises a conductive agent and / or a binder.
9. A positive electrode of a lithium ion battery, comprising a current collector and a positive electrode material composited on the surface thereof, characterized in that: The positive electrode material is the positive electrode material according to claim 8.
10. A lithium ion battery, characterized in that: The positive electrode according to claim 9 is included.
Citation Information
Patent Citations
Lithium-rich manganese-based positive electrode material and preparation method thereof
CN115763688A
Composite sodium ferric pyrophosphate positive electrode material and preparation method thereof
CN116344773A
Positive electrode active material and preparation method therefor, and lithium battery
WO2020258764A1